THE USE OF READ, COVER, REMEMBER, RETELL (RCRR) TO IMPROVE STUDENTS READING COMPREHENSION - Widya Hariyanti; Sella Puspitasari; Juni Adi Saputra (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
This study evaluates the effectiveness of the Read, Cover, Remember, Retell (RCRR) strategy in improving students' reading comprehension skills among seventh-grade students at SMPN 10 Cimahi. Using a quantitative approach with an experimental design, students were divided into an experimental group taught using the RCRR strategy and a control group receiving conventional instruction. Data were collected through pre-tests, post-tests, and questionnaires to measure reading comprehension and students' perceptions of the RCRR strategy. The results showed a significant increase in reading comprehension in the experimental group, with average scores rising from 40.27 in the pre-test to 73.47 in the post-test. Additionally, 68% of students responded positively to the RCRR strategy, highlighting its acceptance and effectiveness. These findings indicate that the RCRR strategy is not only effective in enhancing students' reading comprehension but is also well-received by students, making it a valuable teaching tool for educators.